KONTESTASI PENAFSIRAN IDEOLOGIS DI WEBSITE: STUDI ATAS AYAT-AYAT MUTASHĀBIHĀT SIFAT ALLAH DALAM SITUS ISLAM SALAFI DAN NAHDLATUL ULAMA - Faruq, Umarul (MUSHAF: Jurnal Tafsir Berwawasan Keindonesiaan, 2021)
This article aims to figure out the contesting ideological exegesis of the mutashābihāt verses in the sifāt of Allah from two Islamic sect in Indonesia, Salafi Islam and Nahdlatul Ulama. By using a comparative-qualitative approach to the data on the two streams on the website, this article attempts to describe the interpretations, views, and ideological tendencies of the two schools. Finally, this research concludes that salafi Islam tends to interpret mutashabihat verses zahir without using takwil. Meanwhile, Nahdlatul Ulama carried out takwil on mutashābihāt verses, especially those related to verses that had the connotation of jismiyyah. Although they have differences in interpreting mutashābihāt, they both avoid equating Allah with his being. This article emphasizes that the Salafi Islamic interpretation of the Qur'an and hadith tends to be textual rather than the Nahdlatul Ulama which is more contextual.